Evaluation of the inflammatory markers CCL8, CXCL5, and LIF in patients with anastomotic leakage after colorectal cancer surgery - Klupp, Fee; Schuler, S.; Kahlert, Christoph; Halama, Niels; Franz, Clemens; Mayer, Philipp; Schmidt, Thomas; Ulrich, Alexis (International journal of colorectal disease, 2020)
Anastomotic leakage constitutes a dreaded complication after colorectal surgery, leading to increased morbidity and mortality as well as prolonged hospitalization. Most leakages become clinically apparent about 8 days after surgery; however, early detection is quintessential to reduce complications and to improve patients’ outcome. We therefore investigated the significance of specific protein expression profiles as putative biomarkers, indicating anastomotic leakage.
Gesehen am 07.12.2021